Effects of Oocyte Cytoplasmic Central Granulation on Embryonic Development, Blastocyst Formation, and Pregnancy Outcome in Assisted Reproductive Technology and Its Mechanism: Oocyte cytoplasmic central granulation on assisted reproductive - Zhang, Lili; Zeng, Li; Liu, Hong; Jia, Hongxiang; Wu, Yong; He, Chihua (Cellular and Molecular Biology, 2022)
To investigate whether oocyte centrally located cytoplasmic granulation (CLCG) affects embryonic development, blastocyst formation, and pregnancy outcomes in assisted reproductive technology, fifty patients with CLCG in all oocytes were selected as the CLCG group. Then, 150 patients with no abnormal oocyte morphology were randomly recruited as the control group. Both groups underwent laparoscopy, hysterosalpingography (HSG), vaginal ultrasound, and male semen examination. The down-regulation regimen was selected regarding the patient’s ovarian reserve. The egg maturation rate, normal fertilization rate, cleavage rate, available embryo rate, and high-quality embryo rate in the CLCG group were greatly inferior to those in the control group, with remarkable differences (P< 0.05). CLCG grading of oocytes after 30 cycles in the CLCG group indicated that there were 36 cases in the mild group and 14 cases in the severe group. The egg maturation rate in the mild group was lower than that in the severe group, with a notable difference (P< 0.05). The fertilization rate, cleavage rate, available embryo rate, and high-quality embryo rate in the mild group were higher than those in the severe group, with a notable difference (P< 0.05). Compared with the control group, there was no considerable difference in the implantation rate, clinical pregnancy rate, and abortion rate between the CLCG group (P> 0.05). In summary, oocyte CLCG may affect fertilization, embryonic development, and blastocyst formation, but not pregnancy outcomes.